Keep on growing: building and patterning leaves in the grasses. (February 2016) - Lewis, Michael W; Hake, Sarah
Highlights: The ligule transcriptome shares similarities with organ primordia boundaries. Cell cycle genes function at the ligule to optimize leaf angle. A TCP transcription factor regulates LG1. Regulation of LG1 is a domestication trait in rice. Abstract : Monocot leaves have unique features that arise early in their development. Maturing leaves protectively enclose younger leaves and the meristem, the pool of founder cells from which a leaf emerges. Through the maturation process, proximal sheath and distal blade tissues differentiate and are separated by the ligule and auricle structures. Here we review current research focusing on the contribution of gene regulatory factors and phytohormones on the patterning and differentiation of monocot leaves primarily focusing on research in the grasses ( Poaceae ). The 10 000 members of the grasses include the true grain cereals (wheat, rice, maize, etc.), biofuel crops such as sugarcane, pasture grasses, and bamboo. They are the most studied of the monocots due to their tremendous agricultural and agronomic importance.